Psoriatic arthritis treatment regimens, therapy duration and reasons for cessation in the biologics era: a multi‐centre Australian study. (21st July 2017) - Tymms, Kathleen; Kelly, Ayano; Bird, Paul; Griffiths, Hedley; de Jager, Julien; Littlejohn, Geoff; Louw, Sandra; Roberts, Lynden; Youssef, Peter; Zochling, Jane; Nichols, Dave
Abstract: Aim: To describe the treatment regimens, duration of therapy and reasons for disease‐modifying antirheumatic drug (DMARD) cessation in a large psoriatic arthritis (PsA) cohort. Methods: A retrospective non‐interventional multi‐centre study using Audit4 electronic medical records, with de‐identified, routinely collected clinical data from rheumatology practices in the OPAL consortium (Optimising Patient outcomes in Australian rheumatoLogy) during November 2015. Baseline characteristics, type and duration of conventional and biologic DMARDs (cDMARD and bDMARD, respectively), disease activity (Disease Activity Score of 28 joints C‐reactive protein [DAS28‐CRP]), and reasons for treatment cessation were recorded. Results: A total of 3422 rheumatologist‐diagnosed PsA patients were included: 60% female, mean age 54 years and disease duration 10 years. Of patients with treatment recorded ( n = 2948), 46% were on cDMARD monotherapy, 19% bDMARD monotherapy, 13% combination bDMARD and cDMARDs, 11% combination cDMARDs and 10% no DMARDs. Of those with DAS28‐CRP results ( n = 494), the highest mean DAS28‐CRP was 3.32 on combination cDMARDs, and the lowest was 2.19 on bDMARD monotherapy. Median duration on cDMARD monotherapy was 33.5 months ( n = 2232), on bDMARD monotherapy 110.1 months ( n = 751), on combination bDMARD and cDMARDs 68.5 months ( n = 559). The most common reasons for cessation of cDMARD monotherapy was adverse reactions (41%), for bDMARD monotherapy lack of efficacy (26%), and for combination bDMARD and cDMARDs treatment completed or no longer required (37%). Conclusion: Most PsA patients were prescribed DMARD therapies with a large proportion receiving cDMARDs. Patients on combination cDMARD therapies had the highest DAS28‐CRP results. Adverse reactions were the most common reason for cessation of cDMARD monotherapy, whereas for bDMARD monotherapy it was lack of efficacy.